Investments in Clothing Industry Companies on The Warsaw Stock Exchange During the Covid-19 Pandemic and During the War Between Russia and Ukraine - Frączek, Jędrzej (Journal of Finance and Financial Law, 2024)
The purpose of the article. The Covid-19 pandemic and the war between Russia and Ukraine have disrupted the economic activities of many entities operating in various industries and increased uncertainty in financial markets. The aim of the research was to identify companies from the clothing industry listed on the Warsaw Stock Exchange (WSE) in terms of investment results (profitability and risk) in crisis conditions. Methodology. With respect to the above-mentioned purpose, the following research questions were formulated: PB1. Were there any differences in the profitability and risk of investments in clothing industry companies listedon the Warsaw Stock Exchange during the Covid-19 pandemic and during the war between Russia and Ukraine compared to the period before these events? PB2. Do companies from the clothing industry offer a chance to achieve better investment results compared to investing in the broad market represented by the WIG 20 index? The research is exploratory; therefore, no research hypotheses have been formulated. The research was carried out in two stages: The first stage involved identifying the specificity of companies from the clothing industry listed on the WSE. This part of the research was based on literature analysis, critical literature analysis and document analysis. The second stage consisted in conducting a comparative analysis (in time and space) of the rates of return and risk of the WIG20, WIG-Odzież indexes and companies from the WIG-Odzież index. Data for the period 2017–2023 used in the research, i.e. daily quotations of WIG-Odzież index companies and WIG-20 index, come from the historical data section of the online financial website stooq.pl. Results of the research. The research conducted indicates: diversity in the operating model, business profile/product range and groups of potential final consumers of clothing industry companies listed on the WSE; differences in the profitability level and risk level of investments in clothing industry companies listed on the WSE during the pandemic and during the war between Russia and Ukraine compared to the period before these events. At the same time, differences were noted in the financial results achieved and the risk borne by investors investing their capital in shares of individual companies. Investments in companies from the WIG-Odzież index, compared to investing in the broad market represented by the WIG20 index, are characterized by higher risk and very diversified profitability.